The influence of postflowering pests on cowpea seed yield with particular reference to damage by Heteroptera in southern Benin - Dreyer, H.; Baumgaertner, J.U. (Elsevier, 1995)
Stage-specific survival rates of cowpea seeds were evaluated in fields planted during both cropping seasons of 1991 and 1992 in southern Benin using Manly's regression model. Considerable seed damage could be recognised in all seed growth stages and reflected the variable pest infestations during a cropping season. An analytical approach based on the concept of competing risks and originating from human demography was used to assess the seed damage by the pod sucking bugs (PSB), Maruca testulalis and Apion varium during different stages of pod formation in the presence and absence of other pests. The damage pattern created by an individual pest acting alone changed considerably when competition was taken into account. The risk analysis revealed that an increase in seed damage by a pest of a factor five was possible when others were excluded. It showed that the control of one pest alone is unlikely to reduce seed damage to an acceptable level. Seed damage by the PSB was observed during all stages of pod formation. Heavy seed attack by this pest group during early pod formation reduced available food for other pests in many fields and consequently masked their real damage potential. Clavigralla tomentosicollis was the most damaging PSB species in 11 out of 16 fields in the study area.